Pemberdayaan Kelompok Tani dalam Upaya Peningkatan Ketahanan Pangan - Ida Ayu Putri Astiti; Joko Winarno; Eksa Rusdiyana (Jurnal Sosial Ekonomi Pertanian, 2021)
The research was aimed to analyze the support and the factors causing the lack of support and formulate solutions to support the empowerment of the Tandur Tukul Farmer Group to increase food security in horticulture and fisheries in Joyosuran-Pasar Kliwon, Surakarta City. Using descriptive-qualitative research method, this research was conducted in Tandur Tukul Farmer Group, Joyosuran. the informants were determined by purposive and snowball techniques bu collecting data through interviews, observation, and documentation. The data were analyzed using Milles and Huberman’s interactive inductive model and validated using triangulation of sources and review of informants. The results showed that the empowerment of the Tandur Tukul Farmer Group was supported by the chairman and members of the farmer group, community leaders, Joyosuran Community-Based Disaster Alert organization, Joyosuran Village Government, field agricultural extension workers, the Department of Agriculture, Food Security and Fisheries Surakarta, and Joyosuran Village Community Empowerment Institution in the form of material and non-material. Factors causing the lack of support are related to the lack of knowledge on plant cultivation and fisheries and ineffective communication. The solution to support this empowerment is by conducting comparative studies and strengthening the capacity of the farmer group and its human resources.